The Effect Of Service Quality On Customer Satisfaction, Attitude, And Loyalty Of Pt Pln (Persero) Up3 Rantauprapat - Bobby Fadillah, Muhammad; Taufik Hidayah, Riski (International Journal of Science, Technology & Management, 2025)
PLN stands for PT Perusahaan Listrik Negara (Persero), which is the largest electricity service provider in Indonesia. PLN is a State-Owned Enterprise (BUMN) that plays an important role in providing electricity to the community and industry throughout Indonesia. Every region in Indonesia has a PLN office that functions to serve every community that is a customer of PLN itself, one of which is in the Rantauprapat area which has a PLN (Persero) UP3 Rantauprapat office with many Customer Service Units (ULP) spread across each region as many as 8 customer service units, namely ULP Tanjung Balai, ULP Simpang Kawat, ULP Aek Kanopan, ULP Aek Kota Batu, ULP Rantauprapat Kota, ULP Aek Nabara, ULP Labuhan Bilik and ULP Kota Pinang and with a total of registered customers as many as. However, behind the large number of customers, there are many complaints submitted by customers of PT PLN (Persero) UP3 Rantauprapat which indicate that PT PLN (Persero) UP3 Rantauprapat provides poor service quality which will affect user satisfaction, attitude and loyalty. The purpose of this study is to determine the quality of service from PT PLN (Persero) UP3 Rantauprapat which is perceived by looking at the quality of service, satisfaction, attitude and loyalty of PT PLN (Persero) UP3 Rantauprapat customers. This study uses a quantitative method using a questionnaire using a google form which is distributed to respondents using a purposive sampling technique. Valid and reliable data from 419 respondents were analyzed using structural equation modeling with the help of SmartPLS 4.1.1.2. The results of the study show that the response from respondents for all dimensions and variables has a very good value. Statistical tests show that the Service Quality variable has a significant positive effect on Satisfaction, the Service Quality variable has a significant positive effect on Loyalty, the Satisfaction variable has a significant positive effect on Attitude, the Satisfaction variable has a significant positive effect on Loyalty, the Satisfaction variable has a significant positive effect on Attitude, the Attitude variable has a significant positive effect on Loyalty. The determination coefficient using R-Square shows that there is an influence of Satisfaction of 82.3% on Attitude, an influence of Service Quality of 78.8% on Loyalty, an influence of Service Quality of 78.5% on Satisfaction. The results of this study suggest to PT PLN (Persero) UP3 Rantauprapat to improve the quality of service to customers as a whole, including standardizing uniforms and official vehicles for each officer who directly interacts with customers and conducting socialization of the reporting flow according to the right field to answer customer needs so that it can improve the assessment of the quality of service provided.